Grain and sweet sorghum (Sorghum bicolor L. Moench) serves as a novel source of bioactive compounds for human health. Issue 17 (22nd November 2018) - Vanamala, Jairam K. P.; Massey, Aaron R.; Pinnamaneni, Srinivas Rao; Reddivari, Lavanya; Reardon, Kenneth F.
ABSTRACT: Grain sorghum is an important staple food crop grown globally while sweet sorghum is increasingly considered as a promising biofuel feedstock. Biofuels are the major economic products from the processing of large quantities of biomass, which is currently being utilized to make value-added products in the biorefinery approach. To date, these value-added products are typically commodity chemicals and waste materials used in agriculture. However, there are opportunities to generate high-value bioactive compounds from sorghum grain and biomass. Chronic diseases, such as cancers, are the top causes for morbidity and mortality in developed nations and are promoted by inflammation and oxidative stress. Globally, colorectal cancer results in approximately one-half million deaths annually. It is estimated that as much as 80% of colorectal cancer cases can be attributed to environmental and dietary factors. The sorghum grain and ligno-cellulosic biomass generated for biofuel production has been reported to be high in bioactive compounds, including phenolic acids and flavonoids, with antioxidant and anti-inflammatory properties. This review focuses on the bioactive compounds of grain and sweet sorghum ( Sorghum bicolor L. Moench), for their anti-inflammatory, antioxidant, anti-colon cancer, and immune modulator functions. The review summarizes previous efforts to identify and quantify bioactive compounds in sorghum and documents their anti-cancer biological activities. Finally, this review discusses bioactive compound extraction methodologies and technologies as well as considerations for incorporating these technologies into current biorefining practices.